Role of Endoscopic Ultrasound-Guided Fine-Needle Aspiration of Portal Vein Thrombus in the Diagnosis and Staging of Hepatocellular Carcinoma - Dina Eskandere; Hazem Hakim; Magdy Attwa; Wagdi Elkashef; Ahmed Youssef Altonbary (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims Malignant portal vein thrombus (PVT) is found in up to 44% of patients with hepatocellular carcinoma (HCC). The nature of the thrombus influences treatment selection. The aim of this study was to assess the safety and efficacy of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) in determining the nature of PVT in liver cirrhosis and/or HCC. Methods A prospective study was conducted in 34 patients with liver cirrhosis and/or HCC with PVT. Under EUS guidance, PVT was punctured using a 22 G FNA needle (Cook Medical, Bloomington, IN, USA) followed by monitoring of the puncture tract using color Doppler. Patients were followed for adverse events 2 hours after recovery. Results Throughout the 30-month study period, 34 patients, including 24 males with a mean age of 59±8 years, were enrolled. There were 8 patients with known HCC and 26 with no liver masses detected by computed tomography (CT). EUS-FNA from PVT was positive for malignancy in 3 patients (8.8%), of which only 1 patient was diagnosed with HCC by CT and 2 patients were newly diagnosed with HCC after EUS-FNA. No major complications were reported. Conclusions EUS-FNA is a safe and effective technique for determining the nature of PVT that does not fulfill the malignant criteria via imaging studies in patients with liver cirrhosis and/or HCC.